2003
DOI: 10.1179/joc.2003.15.5.472
|View full text |Cite
|
Sign up to set email alerts
|

Taxanes Synergize with the Bispecific Antibody MDXH447 to Enhance Antibody-Dependent Cell-Mediated Cytotoxicity

Abstract: The interaction between antibody based therapy and cytotoxic chemotherapy is complex. To explore these interactions we investigated, in vitro, the effects of IC 20 growth inhibitory concentrations of taxanes on bispecific antibody-mediated tumor cell cytotoxicity. MDXH447 is a bispecific antibody with specificity for the high affinity IgG receptor (CD64) and the type I epidermal growth factor receptor type (EGF-R). A431 cells, an epidermoid carcinoma cell line that over expresses EGF-R, were exposed to a range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…used chemotherapy to sensitize tumor targets to cytotoxicity mediated by bi-specific antibodies that were directed to T cells [ 32 ]. Tretter reported that taxanes could sensitize BiAb killing [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…used chemotherapy to sensitize tumor targets to cytotoxicity mediated by bi-specific antibodies that were directed to T cells [ 32 ]. Tretter reported that taxanes could sensitize BiAb killing [ 33 ].…”
Section: Introductionmentioning
confidence: 99%